Microscopy and strength of borosilicate glass-to-Kovar alloy joints - Chanmuang C. (2014)
The microstructural basis of the strength of borosilicate glass-to-Kovar alloy joints has been investigated where the alloy was preoxidised at 750 °C for 10 min in air. X-ray diffraction revealed that the oxide scale consisted of hematite and magnetite. Glass was bonded to the alloy by melting at 1000 °C for 15 min under two conditions: (a) ambient atmosphere and (b) vacuum (360 mbar). Scanning and transmission electron microscopy revealed an iron oxide interlayer in the joint bonded under normal atmosphere. Dendritic fayalite nucleated on the iron oxide interlayer and grew into the glass. In the joint made under vacuum, neither the interlayer nor the fayalite phase was observed. In both cases, Co and Ni in the alloy were not involved in the chemical bonding. The joint formed under vacuum had a higher bonding strength of 4.3 MPa, compared to 3.6 MPa for the joint bonded under ambient atmosphere. © 2007 Elsevier B.V. All rights reserved.